Peran Brand Trust Dalam Memediasi Pengaruh Online Customer Review dan Brand Image Terhadap Purchase Decision: (Studi Kasus Pada Hand & Body Lotion Marina di Kota Tangerang) - Imas Amalia; Lutfi Lutfi; Enok Nurhayati (MANAJEMEN, 2025)
The skincare industry in Indonesia has grown rapidly alongside globalization, leading to intense competition among brands. Marina, a local hand & The Indonesian skincare industry is rapidly growing, creating intense competition among brands. Marina, a local hand & body lotion brand established in 1981, is experiencing declining sales due to competitor innovations and stronger brand positioning. This study investigates the mediating role of brand trust in the effect of online customer reviews and brand image on purchase decisions for Marina products in Tangerang. The research involved 180 respondents selected through purposive and accidental sampling. Data were processed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The findings show that: (1) online customer reviews positively and significantly affect purchase decisions, (2) brand image has no direct effect on purchase decisions, (3) both online reviews and brand image significantly influence brand trust, (4) brand trust positively affects purchase decisions, and (5) brand trust mediates the relationship between online reviews, brand image, and purchase decisions. These results highlight the importance of building brand trust as a key strategy. Managing credible online reviews and maintaining product quality consistency can enhance consumer confidence, foster loyalty, and sustain competitiveness in the skincare market.